(untitled) (Journal of Organizational Psychology, 2023)
Action-state orientation (ASO) is a self-regulatory motivational difference reflecting the extent to which individuals will initiate action, avoid distractions, and persist in the face of obstacles or failure. Although differences in action- and state-oriented members are likely to harm team outcomes, the impact of ASO diversity on team functioning has not been explored. Therefore, this study examined the effects of ASO diversity on team relationship conflict, as well as the moderating effects of transition processes and interpersonal processes. Results indicated that teams with high levels of ASO diversity (i.e., having a mixture of action-oriented and state-oriented members) reported higher levels of relationship conflict. Further, interpersonal processes, but not transition processes, moderated the ASO diversity-relationship conflict link. These results draw attention to a novel form of team diversity that increases interpersonal disagreement and emotional friction between members as well as identify a means of mitigating these effects through processes that facilitate confidence building, affect management, and conflict resolution.